Use of Means of Information and Communication Technologies for Formation of the German Competence in Reading Mass Media Texts in Future Philologists - Iryna Ferenchuk (Pedagogical Discourse, 2016)
The use of the Moodle e-learning management system for formation of the German competence in reading mass media texts in future philologists. It systematizes terminology providing the definitions of such notions as information and communication technologies, Moodle e-learning management system, information and communication educational environment. As a result of research the structured requirements to information and communication technologies (ICT) were revealed and the conditions promoting realization of didactic potential of means of ICT in formation of the German competence in reading mass media texts in future philologists. The fundamental position in this question is taken by process of creation of the information and communication educational environment – set of subjects and the objects of educational process providing effective realization of modern educational technologies, the educational results focused on improvement of quality. The information and communication educational environment Moodle is considered as informational product developed on the base of Internet-technologies that provides the interaction among the participants of learning process. The Moodle e-learning management system has considerable capability for developing a methodology of formation of the German competence in reading mass media texts in future philologists and organizing students’ independent work. The author shares the experience of organizing the teaching process in the most effective way.Key words: information and communication technologies (ICT), Moodle e-learning management system, information and communication educational environment.